1995
DOI: 10.1016/0160-2896(95)90032-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain size and cerebral glucose metabolic rate in nonspecific mental retardation and down syndrome

Abstract: Brain size and cerebral glucose metabolic rate (GMR) were determined with magnetic resonance imaging (MRI) and positron emission tomography (PET) in individuals with mild mental retardation (MR), individuals with Down syndrome (DS) without dementia and in matched controls. The MRI data showed that the MR and the DS groups both had brain volumes of about 80% of controls; variance was greatest within the MR group. PET was obtained with [ 18F]-fluorodeoxyglucose (FDG) as the tracer during a test of attention (Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 44 publications
3
23
0
1
Order By: Relevance
“…Whether these areas are unique to pre-clinical AD in DS or represent a very early stage of AD in general can not yet be determined, although there is some VBM evidence of caudate and thalamus atrophy in AD (Karas, Burton et al 2003). Increased regional GMR is also consistent with earlier PET studies showing higher GMR related to poor or inefficient performance of complex cognitive tasks (Haier, Siegel et al 1988;Haier, Siegel et al 1992;Haier 1993;Haier, Chueh et al 1995).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Whether these areas are unique to pre-clinical AD in DS or represent a very early stage of AD in general can not yet be determined, although there is some VBM evidence of caudate and thalamus atrophy in AD (Karas, Burton et al 2003). Increased regional GMR is also consistent with earlier PET studies showing higher GMR related to poor or inefficient performance of complex cognitive tasks (Haier, Siegel et al 1988;Haier, Siegel et al 1992;Haier 1993;Haier, Chueh et al 1995).…”
Section: Discussionsupporting
confidence: 72%
“…Since middle-aged people with Down syndrome (DS) are at increased risk for dementia thought to be of the Alzheimer's type (Wisniewski, Dalton et al 1985;Oliver and Holland 1986;Lott and Head 2001), structural or metabolic brain changes in DS, especially in the temporal lobes and/or posterior cingulate, may predict the onset of dementia. There is some functional brain imaging evidence to support this view (Schapiro, Ball et al 1988;Deb, de Silva et al 1992;Haier, Chueh et al 1995;Dani, Pietrini et al 1996;Pietrini, Dani et al 1997). However, these studies showed inconsistent results, often based on small sample sizes (and often without normal controls), and relied on early PET imaging techniques lacking cognitive activation and/ or precise anatomical localization of findings.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Haier et al (1995) tested the brain efficiency hypothesis by using MRI to measure brain volume and glucose metabolic rate to measure 253 RACE DIFFERENCES IN COGNITIVE ABILITY glucose uptake (an indicator of energy use). They found a correlation of -.58 between glucose metabolic rate and IQ, suggesting that more intelligent individuals have more efficient brains because they use less energy in performing a given cognitive task.…”
Section: Race Differences In Cognitive Abilitymentioning
confidence: 99%
“…Aberrant fiber tracts in left posterior temporo-parietal cortices covary with children's and adults' reading skills, with higher fractional anisotropy and coherence indexes coinciding with better reading skill (Deutsch et al, 2005; Klingberg et al, 2000). Likewise, failures in neural pruning might produce overabundant synaptic connections in a cortical region, contributing to increased neural activity in this region (Haier et al, 1995). However, thicker myelin sheaths and larger axon diameters account for greater white matter volume in normal readers' left posterior STG, providing efficient neural conduction in the left STG (Golestani et al, 2002).…”
Section: Discussionmentioning
confidence: 99%